PERSPECTIVES ON VIDEO GAME RESEARCH THROUGH THE CONCEPT OF MEDIA ARCHAEOLOGY - SKUBINA, Nataliia (Fìlosofìâ ta polìtologìâ v kontekstì sučasnoï kulʹturi, 2024)
This article delves into various approaches to the cultural and philosophical study of video games. It primarily examines the potential of employing methodological foundations of media archaeology to enhance the understanding of the history of video game technical media. Additionally, it offers a brief review of existing publications on the proposed topic.To justify the applicability of the media-archaeological approach, the article provides a concise analysis of key research directions in game studies, highlighting their advantages and main shortcomings. The paper includes a succinct history of video game research, elucidates the philosophical concepts underpinning early works on the essence of video games, and explores the principal directions within game studies. Special attention is given to several approaches: Espen Aarseth’s narratological perspective, which interprets the cyberspace of games as a text that can be decoded and read; Gonzalo Frasca’s ludological approach, where the primary characteristic of a game is its interactivity; and Ian Bogost’s multi-level theory of video game study, which integrates the use of media anthropology.Subsequently, the article outlines the core principles of media anthropology as an interdisciplinary field that not only investigates the past of media and attempts to forecast the future of technologies by identifying patterns in their development but also addresses the relationship between humans and technologies. The primary representatives of this field, such as Friedrich Kittler, Jussi Parikka, and Erkki Huhtamo, are also mentioned.In the final section of the article, the necessity of employing media anthropology for understanding video games is discussed, particularly emphasizing the hegemony of technical media over the content of video games. Furthermore, examples of the application of the archaeological approach in game studies are provided, illustrating the potential of this direction.This comprehensive exploration aims to advance the discourse on video game studies by integrating insights from media archaeology and media anthropology, thereby fostering a deeper and more nuanced understanding of video games as cultural and technological artifacts.